2001
DOI: 10.1016/s1097-2765(01)00207-6
|View full text |Cite
|
Sign up to set email alerts
|

Structural Model for the Cooperative Assembly of HIV-1 Rev Multimers on the RRE as Deduced from Analysis of Assembly-Defective Mutants

Abstract: The functional efficacy of the HIV-1 Rev protein is highly dependent on its ability to assemble onto its HIV-1 RNA target (the RRE) as a multimeric complex. To elucidate the mechanism of multimeric assembly, we have devised two rapid and broadly applicable strategies for examining cooperative interactions between proteins bound to RNA, one based on cooperative translational repression of a two-site reporter and the other on gel shift analysis with crude E. coli extracts. Using these strategies, we have identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

19
188
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(207 citation statements)
references
References 33 publications
19
188
0
Order By: Relevance
“…Biochemical fractionation studies showed that p13 is indeed inserted as integral membrane protein in the inner mitochondrial membrane (see below; [6]). The high flexibility score of the PPTSSRP motif (residues [42][43][44][45][46][47][48] suggests that this might represent a hinge region. The C-terminal region (residues 65-75) is predicted to fold as a b-sheet structure.…”
Section: Amino Acid Sequence and Structural Features Of Htlv-1 P13mentioning
confidence: 99%
“…Biochemical fractionation studies showed that p13 is indeed inserted as integral membrane protein in the inner mitochondrial membrane (see below; [6]). The high flexibility score of the PPTSSRP motif (residues [42][43][44][45][46][47][48] suggests that this might represent a hinge region. The C-terminal region (residues 65-75) is predicted to fold as a b-sheet structure.…”
Section: Amino Acid Sequence and Structural Features Of Htlv-1 P13mentioning
confidence: 99%
“…Rev binds to an elaborate RNA structure, the Rev-response element (RRE), and promotes nuclear export of RRE-containing mRNAs that encode gag/pol and env (Pollard & Malim, 1998). Regions required for RNA binding, trans-activation and multimerization have been mapped within Rev (Daly et al, 1989;Malim & Cullen, 1991;Malim et al, 1989 Malim et al, , 1990Olsen et al, 1990;Pollard & Malim, 1998), but the precise features that determine the specificity and stability of the Rev-multimerization process have yet to be defined fully.An elegant genetic selection was used to identify Rev mutants with deficiencies in the Rev multimeric-assembly pathway (Jain & Belasco, 2001). Three classes of multimerization defect were resolved.…”
mentioning
confidence: 99%
“…Amino acid residues 11-32 of the amino-terminal helix constitute multimerization domain I (MD-I), whereas aa 52-67, which constitute multimerization domain II (MD-II), are part of a second, longer helical region that also includes the Rev RNA-binding domain. The helical regions of MD-I and -II are held together through hydrophobic interactions and amino acid residues comprising the dimerization and trimerization interfaces map to opposite, solvent-exposed sides of the antiparallel helices (Jain & Belasco, 2001). …”
mentioning
confidence: 99%
See 2 more Smart Citations